L'élevage des bovins et l'insémination artificielle en Adamaoua (Cameroun français) - Mandon, A. (1948)
Reports of crossbreeding experiments with Fulani, Red Bororo and Montbeliard cattle. Descriptions of artificial insemination after semen collection, dilution, transportation, preservation and utilisation in Adamawa included.